Peran Jurnal.id dalam Meningkatkan Produktivitas Penjualan dan Pembelian di PT Mitra Sejahtera Membangun Bangsa - Rifky Indi Bakhtiar; Muslimin Muslimin (SUSTAINABLE, 2026)
This article explores how Jurnal.id helped improve the sales and purchase processes at PT Mitra Sejahtera Membangun Bangsa. The research uses a descriptive qualitative method, based on the writer’s direct experience and observation during the internship program. The findings show that the implementation of Jurnal.id significantly increases work efficiency, reduces input redundancy, and improves real-time data integration across divisions. Key features such as automated reporting, clear inventory classification, and a user-friendly interface contribute to faster transaction input, smoother coordination, and more accurate decision-making. These results support previous studies that emphasize the effectiveness of cloud accounting systems in enhancing financial reporting and operational productivity. The study concludes that Jurnal.id functions not only as a transaction recording tool but also as a strategic platform supporting digital transformation in daily business operations.